Transcendence In Sasak Tarekat Literature: A Stylistic Analysis - Aswandikari Aswandikari; Sukri Sukri; Burhanuddin Burhanuddin; Syaiful Musaddat; Suhaib Al Faruq; Muhammad Sastrawan Barmansyah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This research is important to conduct because (1) "pupuh tembang Sasak" is one of the readings of the congregation of the Sasak tarekat assembly in Lombok; (2) "pupuh tembang Sasak" uses many expressions and teaches Sufism so that it is difficult to understand; (3) the Sasak community tends to learn at the inner level. Because, the use of symbols, metaphors, allegories is dominant. This research aims to explain the types and meanings of the language styles used so that the congregation can understand the meaning contained in "pupuh tembang Sasak". Methodologically, this research uses a hermeneutic approach for data analysis and data collection using library methods. There are several forms of expressions used in pupuh tembang Sasak, namely symbolism, metaphor, and allegory. The use of these three types of expressions is in accordance with the characteristics of the congregation of the tarekat which prioritizes inner experience. Expressions in "pupuh tarekat Sasak" use animal names, regional names, natural names, and names of trees and fruits. The use of these expressions through names carries moral and spiritual meanings, including repentance, asceticism, poverty, patience, gratitude, approval, self-awareness, optimism, fear, and longing. Given this, a figure capable of transmitting the expression "pupuh tarekat Sasak" to the Sasak congregation is needed.